Answer: x = -9 , y = 14
Explanation:
3x + 2y = 7 ................ equation 1
4x + 3y = 15 .............. equation 2
Solving using elimination method , we have to decide the variable we are eliminating first , we could eliminate x or y. If we are to eliminate y first , we will multiply equation 1 by 3 and equation 2 by 2 so that the coefficient of y can be the same. The equation then becomes
3( 3x + 2y = 7 )
2 ( 4x + 3y = 15 )
Expanding , we have
9x + 6y = 21 ..................equation 3
8x + 6y = 30 ................ equation 4
Now that the coefficient of y is the same , we will subtract equation 4 from equation 3 to eliminate y , we have
x = -9
Substitute y = -9 into equation 1 to find the value of x , we have :
3( -9 ) + 2y = 7
-27 + 2y = 7
2y = 7 + 27
2y =34
y = 34/2
y = 14